2002
DOI: 10.2135/cropsci2002.1547
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between Growth Traits and Spectral Vegetation Indices in Durum Wheat

Abstract: Destructive sampling for TDM assessment is tedious and time-consuming, and reduces the area available for Future wheat yield improvements may be gained by increasing determining final grain yield in small research plots. total dry matter (TDM) production. Vegetation indices (VI) based on spectral reflectance ratios have been proposed as an appropriate Also, sampling errors often hinder the detection of gemethod to assess TDM and leaf area index (LAI) in wheat. This study notypic differences (Whan et al., 1991)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

12
106
1
4

Year Published

2005
2005
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 163 publications
(123 citation statements)
references
References 41 publications
12
106
1
4
Order By: Relevance
“…These findings have also been supported by satellite based studies which indicated good associations between NDVI and wheat grain yield 50 to 110 days after plant emergence [2,15,19,26,49,50]. This wide time period encapsulates critical phenological phases for predicting the final wheat yield, including the formation and organisation of the canopy structure after the emergence of the flag leaf [8,50], at the end of stem elongation and beginning of heading [47] and grain formation [51]. Other studies [11,14] and those undertaken in Australia [37,49,52] suggest that for cereal crops, biomass or LAI measures at the flowering or anthesis stage (September to November) are closely related to final yield.…”
Section: Wheat Phenology and Image Acquisition Datesupporting
confidence: 54%
See 1 more Smart Citation
“…These findings have also been supported by satellite based studies which indicated good associations between NDVI and wheat grain yield 50 to 110 days after plant emergence [2,15,19,26,49,50]. This wide time period encapsulates critical phenological phases for predicting the final wheat yield, including the formation and organisation of the canopy structure after the emergence of the flag leaf [8,50], at the end of stem elongation and beginning of heading [47] and grain formation [51]. Other studies [11,14] and those undertaken in Australia [37,49,52] suggest that for cereal crops, biomass or LAI measures at the flowering or anthesis stage (September to November) are closely related to final yield.…”
Section: Wheat Phenology and Image Acquisition Datesupporting
confidence: 54%
“…After this stage (during the ripening process) there is an asymptotic relationship between NDVI, LAI and yield [14,46,47]. This indicates that the use of NDVI as a surrogate for biomass and yield prediction is best at crop stages where LAI values are less than 3 [45].…”
Section: Wheat Phenology and Image Acquisition Datementioning
confidence: 98%
“…Various studies in wheat have associated GY with reflectance data from these zones of the spectral signature [17,21,50].…”
Section: Regression Coefficients For Different Spectral Zonesmentioning
confidence: 99%
“…In wheat study of Aparicio et.al. [14] , the correlation of LAI with vegetation index was not affected by planting measures, species or planting area. But such results on tobacco should be verified through further test.…”
Section: Conclusion and Discussionmentioning
confidence: 77%